Communication competence, self-efficacy, and spiritual intelligence: evidence from nurses - Gholamhossein Mehralian; Ali Reza Yusefi; Neda Dastyar; Shima Bordbar (BMC, 2023)
Abstract Introduction Communication skills and acceptable levels of spiritual intelligence (SI) are the prerequisites of the nursing profession, which can significantly impact the individual and organizational performance of nurses. This study aimed to investigate the competency and self-efficacy of communication and its relationship with the SI of nurses. Methods This cross-sectional study was conducted in 2021 and included 312 nurses working in a COVID-19 hospital in the south of Iran. The data collection instruments were the Standard Communication Competence Scale, Communication Self-Efficacy, and SI Questionnaires. Data were analyzed with SPSS software version 23 using descriptive and inferential statistics, and t-test, ANOVA, Pearson's correlation coefficient, and multiple linear regression were performed at 5% significance level. Results The mean scores of nurses' communication competence, communication self-efficacy, and SI were 89.11 ± 7.32 out of 180, 64.45 ± 5.61 out of 120, and 147.13 ± 11.26 out of 210, respectively. A direct and significant correlation was observed between competence (r = 0.527, p<0.001) and communication self-efficacy (r = 0.556, p<0.001) with spiritual intelligence. The dimensions of spiritual intelligence, including the ability to deal with and interact with problems, self-awareness, love and affection, general thinking and doctrinal dimension, and dealing with moral issues, were identified as predictors of nurses' communicative competence and self-efficacy (p<0.05). There was a positive and significant correlation between nurses' competence and self-efficacy with their age (p<0.05). The nurses' mean communication competence and self-efficacy score were different regarding their level of education and the number of shifts (p<0.05). The mean scores of self-efficacy revealed a statistically significant difference between the participants' gender and the number of patients under observation (p<0.05). Moreover, the nurses' SI significantly correlated with age, and the mean scores of this intelligence had statistically significant differences regarding gender (p<0.05). Conclusion The nurses' communication competence and self-efficacy were at a moderate level. Considering the correlation and predictive role of SI and its dimensions, it is recommended to promote problem-solving skills, improve self-awareness, and pay attention to moral standards to nurture communication competence and self-efficacy among nurses.